Pembelajaran Tauhid dan Entrepreneur untuk Anak Usia Dini - Wariati, Wariati; Sukiman, Sukiman (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
TK Khalifah Gedongkuning Yogyakarta has a unique program in developing tawhid-based learning and entrepreneurship for children. This article aims to analyze the implementation of tawhid and entrepreneurship learning in the school. This research focuses on how the concept of tawhid and entrepreneur learning in TK Khalifah Gedongkuning Yogyakarta is, how the learning process is, and how the results are achieved. This type of research is descriptive interpretative qualitative research with a phenomenological approach. The results of this study indicate: First, learning tawhid and entrepreneurship at TK Khalifah Gedongkuning Yogyakarta applies a simultaneous integrative concept by combining tawhid and entrepreneurship learning so that both are mutually reinforcing. Second, the implementation process of learning tawhid and entrepreneurship in TK Khalifah Gedongkuning Yogyakarta uses several methods and program activities. The method used is the method of advice, for example, habituation, singing, and stories or stories. Meanwhile, the program of activities includes outing class, cooking class, and market day. Third, the learning outcomes of tawhid and entrepreneurship are forming an attitude of independence, creativity, discipline, honesty, confidence, and responsibility for students. These findings reference managers of educational institutions and early childhood education teachers to formulate policies and implement monotheism-based learning and entrepreneurship in children.